Commentary: Global Alzheimer's disease and Alzheimer's disease related dementia research funding organizations support and engage the research community throughout the COVID‐19 pandemic. Issue 5 (1st October 2021) - Meyers, Emily A.; Amouyel, Philippe; Bovenkamp, Diane E.; Carrillo, Maria C.; De Buchy, Geraldine Drexel; Dumont, Magali; Fillit, Howard; Friedman, Lauren; Henderson‐Begg, Gregor; Hort, Jakub; Murtishaw, Andrew; Oakley, Richard; et al.
Abstract: The COVID‐19 pandemic has disproportionately affected more vulnerable populations, including those living with dementia. Over 50 million individuals worldwide are living with Alzheimer's disease (AD) or other dementia, and it is crucial to continue the fight against the condition during the global pandemic. Since the start of mandated lockdowns in March 2020, charity and non‐profit organizations that fund AD and related dementia research continue to respond to the needs of the AD research community, ensuring the momentum continues and accelerates. Members of the International Alzheimer's and Related Dementia Research Funder Consortium, a group of nearly 40 funding organizations that informally convene throughout the year to share updates and information, have taken a number of steps to ensure the continued support of the research community. Even during times of uncertainty,  it is essential that the field moves forward to uncover preventions, diagnoses, and treatments for these diseases that affect many millions globally.